Role of intraseasonal oscillation in the persistent extreme precipitation over the Yangtze River Basin during June 1998. Issue 18 (20th September 2016) - Sun, Xuguang; Jiang, Guixiang; Ren, Xuejuan; Yang, Xiu‐Qun
Abstract: The persistent extreme precipitation event (PEPE) that occurred over the Yangtze River Basin (YRB) during the period of 12–27 June 1998 is the most severe one in recent 60 years, and it is mainly caused by two significant components of intraseasonal oscillation (ISO) (10–30 days and 30–60 days) identified in this study. The two ISOs play different roles in the distributions of YRB rain belt in the PEPE; i.e., the 30–60 day ISO generally maintains the shape and intensity of YRB rain belt with its peak covering the whole PEPE period; however, the 10–30 day ISO mainly determines the south‐north swing of the YRB rain belt that features three PEPE stages. North Indian Ocean is the major forcing region of 30–60 day ISO, where anomalous warm sea surface temperature‐induced local strong convections stimulate a meridional teleconnection wave train over the East Asia, generating the 30–60 day intraseasonal YRB rainfalls. The 10–30 day ISO primarily originates from the northwest Pacific and the South China Sea (SCS), and along with its northwestward and northeastward propagations due to the air‐sea coupling and prevailing winds, suppressed and enhanced convections appear alternatively over the Philippine Sea and the central SCS in the three PEPE stages; thus, their stimulated downstream wave trains along the coast of East Asia vary accordingly in terms of phase and position, causing three stages of 10–30 day intraseasonal YRB rainfalls with different intensities and locations. These results suggest that proper combination of different intraseasonal oscillations is one of the essential and effective ways to produce the PEPEs. Key Points: Thirty to 60 day oscillations maintain the intensity of 1998 PEPE, while 10‐30 day oscillations determine the evolutionary characteristics North Indian Ocean and Philippine Sea are the key forcing regions in generating 30‐60 day and 10‐30 day oscillations, respectively Proper combination of different intraseasonal oscillations is one of the essential and effective ways to produce the PEPEs